Determining the Optimal Volume of Petroleum Products in Oil Storage Facilities for Agricultural Enterprises - Tursunov, B. N. (American Journal of Bioscience and Clinical Integrity, 2025)
This article discusses the introduction of a new system to ensure the continuous supply of petroleum products for modern machine-tractor aggregates within the framework of Uzbekistan’s agricultural development strategy in recent years. The primary reason for this system’s implementation is to cultivate agricultural products in a short period, achieve high yields, and reduce production costs. The study focuses on determining the optimal number of fuel and lubrication dispensing units in oil storage facilities.